2019
DOI: 10.1017/s1368980019002192
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns are associated with premenstrual syndrome: evidence from a case-control study

Abstract: Objectives:Premenstrual syndrome (PMS) is a common cyclic psychological and somatic disorder which reduces women’s quality of life. Evidence regarding the association between dietary patterns (DPs) and PMS is rare. The study aimed to determine the relationship between dietary patterns and PMS.Design:The case-control study was conducted among women with confirmed PMS and healthy individuals recruited from healthcare centres.Setting:Dietary data were collected using a validated semi-quantitative food frequency q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
13
0
3
Order By: Relevance
“…Dietary factors are influential but modifiable parameters that can be included in the management of PMS, and several studies have found a significant association between dietary habit and PMS [5,26]. A study conducted in the United Arab Emirates reported a high prevalence of PMS among university students with high calorie/fat/sugar/salt food consumption [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary factors are influential but modifiable parameters that can be included in the management of PMS, and several studies have found a significant association between dietary habit and PMS [5,26]. A study conducted in the United Arab Emirates reported a high prevalence of PMS among university students with high calorie/fat/sugar/salt food consumption [26].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the United Arab Emirates reported a high prevalence of PMS among university students with high calorie/fat/sugar/salt food consumption [26]. Western dietary pattern, which is characterized by high consumption of fast foods, soft drink, and desserts, is significantly associated with a higher likelihood of PMS, whereas healthy and traditional dietary pattern is associated with a lower risk [5,9]. The MD is rich in high-complex carbohydrate and monounsaturated fatty acids, rather than simple sweets and saturated and trans-fatty acids [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 A study published in 'Public Health Nutrition', has documented that diet rich in eggs, tomatoes, meat, fruits, condiments and nuts is associated with alleviating the symptoms of PMS. 27 Bahrami has reported that intake of vitamin D is associated with protective effects that can help prevent symptoms of premenstrual syndrome. 28 Results of a double blind controlled trial in Iran, has stated that Vitamin D and E are both beneficial in relieving the symptoms of premenstrual syndrome.…”
Section: Diet Helpful In Prevention and Severity Of Pmsmentioning
confidence: 99%
“…The western diet which includes burgers, soft drink and processed meat contributes in the development of PMS with highly significant p value of <0.001. 27 Various studies have observed the effects of caffeine in the diet. A research has documented that caffeine in the diet not only cause the PMS but also prolongs its duration.…”
Section: Diet Causing Premenstrual Syndromementioning
confidence: 99%